La Discussion à Visée Philosophique : une pratique d’éducation à une citoyenneté du Care - Christian Budex (Éducation et Socialisation)
The incorporation of Care ethics into the field of pedagogical practices for citizenship education remains, at present, scarcely supported by empirical evidence. To address this gap, we propose a framework for analyzing the manifestations of ethical and civic dispositions at work among participants in a Philosophical Discussion that can be considered as pertaining to the practice of Care. This article presents the results of qualitative research that tests these dispositions against specific markers to show how they are specifically mobilized during a Philosophical Discussion. We will then discuss the conditions under which this framework can be considered an educational activity of Care, an implementation of care and solicitude that initiates the citizen of tomorrow into the actions and situations inherent to the ethical and political ideal of Care.